Search for Higgs and Z boson decays to J/psi or Y pairs in the four-muon final state in proton-proton collisions at root s=13 TeV - CMS Collaboration; Damarseçkin, Serdal (ELSEVIER, 2019)
A search for decays of the Higgs and Z boson to pairs of J/ψor Y(nS)(n =1, 2, 3) mesons, with their subsequent decay to μ+μ−pairs, is presented. The analysis uses data from proton-proton collisions at √s=13 TeV, collected with the CMS detector at the LHC in 2017 and corresponding to an integrated luminosity of 37.5 fb−1. While an observation of such a decay with this sample would indicate the presence of physics beyond the standard model, no significant excess is observed. Upper limits at 95% confidence level are placed on the branching fractions of these decays. In the J/ψpair channel, the limits are 1.8 ×10−3and 2.2 ×10−6for the Higgs and Z boson, respectively, while in the combined Y(nS)pair channel, the limits are 1.4 ×10−3and 1.5 ×10−6, respectively, when the mesons from the Higgs and Z boson decay are assumed to be unpolarized. When fully longitudinal and transverse polarizations are considered the limits reduce by about 22–29% and increase by about 10–13%, respectively.©2019 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license
Keywords: CMS; Standard model physics; Higgs boson; Z boson; Rare decays